2014
DOI: 10.1111/bjd.13305
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence mapping in inherited epidermolysis bullosa: a study of 86 cases from India

Abstract: This is the first large study of IFM of the subtypes of EB in Indian patients. The study provides a framework for better understanding of EB in Indian patients and for better diagnosis and management, particularly in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 13 publications
2
31
0
2
Order By: Relevance
“…Although easily accessible and successfully implemented in many countries, IFM is not readily available in India due to lack of infrastructure and financial constraints. The purpose of IFM is to classify EB into its major types and identify a candidate gene that can be screened for potentially pathogenic variations [3,4,[7][8][9][10][11] . Without an extended panel of antibodies, it will be difficult to achieve this in resourcelimited settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although easily accessible and successfully implemented in many countries, IFM is not readily available in India due to lack of infrastructure and financial constraints. The purpose of IFM is to classify EB into its major types and identify a candidate gene that can be screened for potentially pathogenic variations [3,4,[7][8][9][10][11] . Without an extended panel of antibodies, it will be difficult to achieve this in resourcelimited settings.…”
Section: Discussionmentioning
confidence: 99%
“…Till date, only 5 case series showed the utility of IFM and other nonmolecular tests in establishing a diagnosis of EB [3,4,[7][8][9] . Recently, Hiremagalore et al [8] published the only and largest series of IFM studies in EB patients from India and reported a concordance of only 57% using a similar limited panel of antibodies. We feel that comparison with clinical diagnosis, that is known to be variable, could be the reason for such a low concordance [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 In the present study, overall concordance of clinical and laboratory diagnosis was 88.5%, while the respective percentage of the study in India was 57%. 20 The high rate of concordance is attributed to the small number of infants in the present study and to the fact that all IFM results were conclusive.…”
Section: Discussionmentioning
confidence: 56%
“…[1][2][3][4]8,10,12,14,15,20 To our knowledge, patient with JEB, gen-i, who presented demyelinating disease (multiple sclerosis) has not been described in literature until present day.…”
Section: Discussionmentioning
confidence: 99%